2002
DOI: 10.1006/mthe.2002.0639
|View full text |Cite
|
Sign up to set email alerts
|

Evidence of CFTR Function in Cystic Fibrosis after Systemic Administration of 4-Phenylbutyrate

Abstract: Most individuals with cystic fibrosis (CF) carry one or two mutations that result in a maturation defect of the full-length protein. One such mutation, deltaF508, results in a mutant membrane glycoprotein that fails to progress to the apical membrane, where the wild-type protein normally functions as a cyclic AMP-regulated chloride channel. 4-Phenylbutyrate (Buphenyl), an orally bioavailable short chain fatty acid, modulates heat shock protein expression and restores maturation of the deltaF508 protein in vitr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
129
0
1

Year Published

2008
2008
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 177 publications
(133 citation statements)
references
References 24 publications
3
129
0
1
Order By: Relevance
“…31 4-PBA has been demonstrated to reduce the load of mutant or mislocated proteins retained in the ER under conditions associated with cystic fibrosis and liver injury. 25 It is also reported that 4-PBA has a neuroprotective effect on cerebral ischemic injury in a mouse model of ischemia/hypoxia. 27 In the present study, we showed that 4-PBA attenuated hypoxiainduced apoptosis in BSMCs.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…31 4-PBA has been demonstrated to reduce the load of mutant or mislocated proteins retained in the ER under conditions associated with cystic fibrosis and liver injury. 25 It is also reported that 4-PBA has a neuroprotective effect on cerebral ischemic injury in a mouse model of ischemia/hypoxia. 27 In the present study, we showed that 4-PBA attenuated hypoxiainduced apoptosis in BSMCs.…”
Section: Discussionmentioning
confidence: 96%
“…A previous report showed that 4-PBA facilitates normal trafficking of mutant proteins from the ER to the plasma membrane. 25 Other reports also showed that 4-PBA has chemical chaperone activity and protects the brain against ischemic injury and ER stress-induced neuronal death in vivo and in vitro. 26,27 Using 4-PBA, we first examined whether ER stress triggered by tunicamycin and thapsigargin, known inducers of ER stress, is attenuated by 4-PBA in BSMCs.…”
Section: Attenuation Of Hypoxia-induced Apoptosis In Vitro and Boo-inmentioning
confidence: 97%
“…Butyrate nonspecifically improves ΔF508 CFTR protein expression and function but also promotes expression of many other proteins in the cell. This has led to the development of orally bioavailable sodium 4-phenylbutyrate, which demonstrated borderline promising results in a pilot study involving patients homozygous for ΔF508 CFTR [93]. However, these improvements were not augmented with dose escalation and led to unacceptable adverse effects [93].…”
Section: Restoration Of Cftr Expression or Functionmentioning
confidence: 99%
“…This has led to the development of orally bioavailable sodium 4-phenylbutyrate, which demonstrated borderline promising results in a pilot study involving patients homozygous for ΔF508 CFTR [93]. However, these improvements were not augmented with dose escalation and led to unacceptable adverse effects [93]. A phase II clinical trial is underway in CF patients harboring the G551D CFTR allele, which produces a poorly functional CFTR protein in the cell membrane.…”
Section: Restoration Of Cftr Expression or Functionmentioning
confidence: 99%
“…We have studied potential transnitrosation targets in the CFTR interactome (3,22) of relevance to CFTR trafficking. Here, we report that GSNO S-nitrosylates heat shock protein (Hsp)70/ Hsp90 organizing protein (Hop)-also known as stress-induced phosphoprotein 1 (Stip-1) (23)-decreasing Hop expression and decreasing the association between Hop and maturing CFTR.…”
mentioning
confidence: 99%